Trisubstituted-imidazoles induce apoptosis in human breast cancer cells by targeting the oncogenic PI3K/Akt/mTOR signaling pathway - Mohan C.D. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0153155